PARTICIPAÇÃO DOS Staphylococcus spp NA ETIOLOGIA DAS MASTITES EM BOVINOS LEITEIROS NO ESTADO DE PERNAMBUCO (BRASIL) - Rinaldo Aparecido Mota; Elizabeth Sampaio de Medeiros; Marcos Veiga dos Santos; José Wilton Pinheiro Júnior; Andrea Paiva Botelho Lapenda Moura; Luciana Cavalcanti Arruda Coutinho (Ciência Animal Brasileira, 2012)
The purpose of this study was to quantify the occurrence of the bacteria Staphylococcus in the etiology of bovine mastitis in the state of Pernambuco (Brazil). A total of 1,080 samples were collected from 15 farms located in Zona de Mata, Agreste, and Metropolitan Recife Regions of the State of Pernambuco. Milk samples were spread on an agar base enriched with 5% sheep’s blood and incubated at 37ºC, with readings at 24, 48 and 72 hours. The morphological characteristics of the colonies were used to identify the bacteria, as well as the morphostaining chacteristics, using the Gram technique. Biochemical tests were carried out, such as production of free coagulase, DNase, catalysis, acetonin production test, glucose (anaerobiose) and manitol (aerobiose and anaerobiose) fermentation. Of the 1,080 samples analyzed, 740 (68.5%) were positive upon microbiological examination and 340 (31.5%) negative. The Staphylococcus bacteria were isolated in 291 (39.3%) of the samples. Of these, 170 (58.4%) were classified as coagulase-negative Staphylococcus (SCN), 84 (28.9%) as Staphylococcus aureus (S.aureus) and 37(12.7%) as coagulase-positive Staphylococcus (SCP). The results of the present study indicated that Staphylococcus spp has a high participation in the epidemiology of bovine mastitis in the region selected and suggests that medium and long-term training take place to prepare specialists to control and prevent contagious mastitis.